Does the tumor necrosis factor a predictor factor in patients with chronic hepatitis B and C - Bilgic, Yilmaz; Seckin, Yuksel; Cagin, Yasir Furkan; Yildirim, Oguzhan; Yilmaz, Cengiz; Harputluoglu, Murat; Sahin, Abdurrahman (Allied Acad, 2017)
Aim: In our research, we aimed to investigate the importance and pattern of Tumor Necrosis Factor (TNF) alpha in response to the combinatorial treatment of lamuvidin (LAM) and Pegile interferon (PEG INF) 2a + Ribavirin (RIB) in patients with Chronic Hepatitis B (CHB) and Chronic Hepatitis C (CHC). Material and method: Thirty four CHB and 25 CHC patient samples were taken before and after the treatment and stored appropriately. CHB patients were treated with LAM and CHC patients were treated with using the combination of PEG INF 2a and RIB. HBV DNA, anti HBe, ALT, AST and TNF alpha results were obtained from CHB patients before and 48th week of the treatment. HCV RNA, ALT, AST and TNF alpha results were also obtained from CHC patients before and in the 6th month of completing the treatment. Responses to the treatment were taken as negative result of HBV DNA in CHB patients after finishing the treatment and as negative result of HCV RNA in CHC patients after 6 months of finishing the 48 weeks of PEG INF treatment. Results: At the level of decreasing TNF-alpha in CHB patients when the group responding to the treatment compared to the group not responding to the treatment, a significant difference was observed in favor of the respondent group (p< 0.0001). At the level of decreasing TNF-alpha in CHC patients when the group responding to the treatment compared to the group not responding to the treatment, a significant difference was also obtained in favor of the respondent group (p< 0.0001). In the analysis for emphasizing the importance of TNF alpha level in response to the treatment in CHB patients, it was found that predicting the response to the treatment of TNF alpha was 78.6% sensitivity and 75% specificity for 68.78 cutoff. In the analysis for emphasizing the importance of TNF alpha level in response to the treatment in CHC patients, it was found that determining the response of TNF alpha to the treatment was 100% sensitivity and 100% specificity for 122.4 cutoff. Conclusions: With the treatment a decrease in TNF alpha is occured in CHB and CHC patients; however, TNF alpha decrease in the groups responding to the treatment is more significant. The results of this research show that TNF alpha level may be an important non-invasive marker for foresight and determining the response to the treatment.
Keywords: Hepatitis B; Hepatitis C; TNF alpha; Lamuvidin; Pegile interferon